Ultra-Wideband Antennas for Wireless Capsule Endoscope System: A Review - Ben Li; Yifan Wang; Junchi Zhao; Jingjing Shi (IEEE Open Journal of Antennas and Propagation)
Wireless capsule endoscopy (WCE) systems are used to capture images of the human digestive tract for medical applications, especially the noninvasive diagnostics and treatments of small intestinal diseases. As an important part of the WCE system, the antenna plays a crucial role in transmitting and receiving data. To transmit diagnostic real-time images from the inside body with high resolution at a high data transmission speed, ultra-wideband (UWB) antenna designs for the WCE system have been proposed by researchers in recent years. However, to the best of our knowledge, there are few papers to systematically review the UWB antennas used in the WCE system. In this paper, a comprehensive review of different UWB antenna designs for WCE system is presented. In-body and on-body UWB antennas are classified according to the radiative performances and structure. Particular attention is also paid to the models used in simulation and experiment, as well as some key performance parameters and technologies in the process of antenna design. This extensive summary of UWB antennas for WCE systems will help to understand the prospects and challenges in this field.